2003
DOI: 10.1097/00000539-200301000-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Ear Sensor for Pulse Oximetry and Carbon Dioxide Tension Monitoring: Accuracy in Critically Ill Children

Abstract: A new combined ear sensor was tested for accuracy in 20 critically ill children. It provides noninvasive and continuous monitoring of arterial oxygen saturation, arterial carbon dioxide tension, and pulse rate. The sensor proved to be clinically accurate in the tested range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…We attribute this to the warming of the measurement side resulting in an increased local perfusion and, hence, well-defined pulsatile signals [20]. In the present study in the peripherally well-perfused patients, the faster response time with regards to the SpO 2 values at the ear versus left index finger by an average of 30 s is mainly site related [22].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We attribute this to the warming of the measurement side resulting in an increased local perfusion and, hence, well-defined pulsatile signals [20]. In the present study in the peripherally well-perfused patients, the faster response time with regards to the SpO 2 values at the ear versus left index finger by an average of 30 s is mainly site related [22].…”
Section: Discussionmentioning
confidence: 73%
“…SpO 2 values are available immediately, while PcCO 2 values need a certain equilibration time. The system is designed to be ‘ready-for-use’ by automated recalibration every time the sensor is placed on the docking station between measurements [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Those initially available for clinical use in the 1980s included the combination of both TC-O 2 and TC-CO 2 monitors. More recently, TC-CO 2 monitors are available as a single TC-CO 2 electrode or as a combined pulse oximeter and TC-CO 2 monitor (Bendjelid et al 2005;Dullenkopf et al 2003;Tschupp and Fanconi 2003). The newer devices incorporate the two monitors into an earclip sensor which has found increased applications in the older pediatric and even the adult population.…”
Section: Educational Aimsmentioning
confidence: 99%
“…These authors demonstrated that there is a linear relationship between cutaneous and true PaCO 2 in the range of 20 to 75 mmHg. At the turn of the new century, Rohling and Biro [24] and Tschupp and Fanconi [25] published the first articles on monitors that incorporated the elements of an optical pulse oximetry sensor with a Severinghaus-type PaCO 2 sensor [26]. Today, the transcutaneous non-invasive estimation of arterial PaCO 2 is commonly accepted and widely used.…”
Section: Non-invasive Measurement Of Blood Gasesmentioning
confidence: 99%